Prevalence of Sports Injuries in Female Elite Kumite Karate Players - Somayeh Mozafari; Ebrahim Ebrahimi; Hashem Piri (Physical Treatments)
Purpose: Karate is one of the most popular martial arts in the world, but its practice carries the risk of injury. This study examines the mechanisms and prevalence of injuries in female elite kumite karate players. Methods: This retrospective study investigated the prevalence of acute and chronic injuries during the last 6 months in black-belt female Karate players. The Oslo standard questionnaire was used in this study. This questionnaire covers musculoskeletal system care, comprising the severity of the injury, the location of the injury, the type of injury, the mechanism of injury, and the time of injury. Results: Results indicated that the knee was the most common location of acute injuries (χ2=248.052, P=0.001), and the lower back was the most common location of chronic injuries (χ2=129.342, P=0.001). Also, the findings showed that acute contact injuries are more prevalent than non-contact injuries (χ2=7.936, P=0.05), and these injuries have occurred more during training (χ2=7.263, P=0.064). In addition, the results demonstrated that sprain and fracture have the highest percentage in acute injuries (χ2=154.356, P=0.001) and other injuries and tendonitis have the highest rate in chronic injuries (χ2=7.263, P=0.064). Conclusion: The knees and lower back are more prone to injury than other body areas. Coaches and athletes should consider preventive programs to help decrease the risk of injury in these areas.